Phytochemical screening and pharmaceutical effect of Teucrium polium L. - HANI Sabrine; OUAGHED Amna; GHERBI Brahim (Université of Eloued, 2025)
Medicinal plants are among the most important natural resources that humans have used since ancient times to treat diseases and promote health, playing a pivotal role in traditional medicine across various cultures. Among these plants, our study focused on Teucrium polium L., which is notable for its morphological diversity and multiple medicinal properties, including antibacterial, anti-inflammatory, antioxidant, wound healing, anti-diabetic, and anticancer activities. Chemical and chromatographic analyses have shown a high presence of therapeutically important compounds. Antioxidant assays such as DPPH and FRAP, along with anti-inflammatory tests, demonstrated significant efficacy of the plant extracts. The DPPH assay revealed an activity of 41.26 mg/mL for the aqueous extract of Teucrium polium L., the FRAP assay showed 71.07 mg/mL, and the anti-inflammatory test recorded 28.10 µg/mL, indicating strong bioactivity. In this context, a novel natural cream was developed based on Teucrium polium L., which exhibited high effectiveness in accelerating wound healing, reducing inflammation, combating infections, stimulating tissue regeneration, and enhancing collagen production in clinical and experimental trials—without any reported side effects— making it a safe and effective natural alternative to conventional topical treatment
Keywords: Teucrium polium L; antioxidant activity; anti-inflammatory activity; healing activity; stimulating collagen production